FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN WASTING PADA BALITA USIA 6-59 BULAN DI DESA LAPANG KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT TAHUN 2024 - Putri, Fiona; Khairunnas; Muliadi, Teuku; Rahma, Cukri (Universitas Cokroaminoto Palopo, 2024)
This research aims to determine the factors that influence the incidence of wasting in toddlers in Lapang Village, Johan Pahlawan District, West Aceh Regency. This type of research is an analytical survey with a cross sectional approach which was carried out from October to November 2024 in Lapang Village, Johan Pahlawan District, West Aceh Regency. The sample consisted of 67 toddlers aged 6-59 months. The sampling technique used in this research is purposive sampling. Data collection through interviews using a questionnaire. From the results of this research, it was found that the factors that influence the incidence of Wasting are History of Diarrhea, Energy Intake, Protein Intake, Family Income and Mother's Knowledge of Basic Feeding Rules. Meanwhile, factors that do not influence are history of ISPA, Fat Intake, Carbohydrate Intake and history of wasting. Exclusive breastfeeding. This study suggests that future researchers can examine other factors that influence the incidence of wasting besides those in this study, such as number of family members, immunization status and sociodemographics.